Latest news from the bonobos: Pan paniscus myths and realities - David Beaune (Revue de Primatologie)
Bonobos are our closest living relatives along with chimpanzees. They attract much attention from anthropologists who want to better understand our primate origins and more recently from the public because of their remarkable behavior and matriarchal social system. New published insights from recent years allow us to better know Pan paniscus. This review describes the most recent findings: bonobos, chimpanzees, and humans ought to be part of the same genus (Homo or Pan) according to our genetics. bonobos have impressive cognitive ability to communicate with lexigram and sign-language, solve problems and use tools. Females have high social status in the group due to female association and coalition. The society is not really characterized by female dominant but rather by co-dominance of associated females. They are not purely egalitarian but non-violent and tolerant. Neither lethal aggression nor infanticide were observed and are not expected. Sex has a pivotal role in this pacifist society, which lacks sexual restrictions with the one exception of incest. Bonobos are probably a key species in forest ecology through their seed dispersal mutualism with plants whose fruits they eat. We continue to discover fascinating biological facts about our cousins who are in danger of extinction. A few of these are described here.